Determining Leadership Managerial Performance Using 360 Degrees Feedback Questionnaire and Path Analysis (Case Study: A Mining Company) - Hery Hamdi Azwir; Saras Sadanti (JIE Scientific Journal on Research and Application of Industrial System, 2016)
Work Accidents are being critical nowadays, as the number of industry increases and following by the number of work accidents also increases. This company has been struggling in hard year as number of severity rate reached the highest since the last six years. Any programs and campaign to control the hazard is being done, but still the number of severity rate is increasing at the end of 2014. According to Domino Theory (Heinrich, 1980), the root cause lies on bad management, then this research come to solve the issue by measuring the effectiveness of management through leadership managerial roles in assessing the managerial skills, trying to solve the problems from management perspective. This research conducts for managerial level at section head level up in 15 jobsites around Indonesia. The assessment for management adopts 360 degrees method as appraisal performance. This method engages four perspectives; their-selves, superior, peer and subordinate. After conduct the questionnaire, the leadership managerial roles toward the managerial skills performance is mapped using path analysis. According to ideal model from 360 degrees perspectives, the leadership managerial roles highly correlated towards managerial skill performance as much as 0,8297 or 83%, where human skills and conceptual skills are directly affect leadership, meanwhile technical skills indirectly influence leadership through human skills. The ideal model of leadership managerial roles required the managerial skills performances according to the coefficient path shows, LD=0,57HS+0,14CS+0,04ε1